2018
DOI: 10.32327/ijmess.7.3.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foreign Direct Investment, Trade, Aid, Remittances and Tourism on Welfare under Terrorism and Militancy

Abstract: The purpose of this study was to determine the effects of Foreign Direct Investment (FDI), trade, aid, remittances and tourism on welfare under terrorism and militancy. Using Nigeria as a case study for the period from 1980 to 2016, this study utilized autoregressive distributed lag (ARDL) bounds testing approach and the Cobb-Douglas production function. The empirical findings showed that, in the short-run, FDI, trade, aid, remittances and tourism had positive significant effects on welfare, even under terrori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…The two studies, to our knowledge, that have made use of data solely on SSA countries have found contrasting results. While Ijaiya and Ijaiya (2004) found that aid had no effect on poverty reduction in SSA, a recent study, Evans and Kelikume (2018) found that aid has a positive impact on poverty both in the short and long runs. Arvin and Barillas (2002) study of some countries in Asia, Latin America, Caribbean, and Africa, found that aid had no impact on poverty reduction in the Africa sub-samples of North Africa and SSA for the period 1975 to 1998 studied.…”
Section: Foreign Aidmentioning
confidence: 95%
See 1 more Smart Citation
“…The two studies, to our knowledge, that have made use of data solely on SSA countries have found contrasting results. While Ijaiya and Ijaiya (2004) found that aid had no effect on poverty reduction in SSA, a recent study, Evans and Kelikume (2018) found that aid has a positive impact on poverty both in the short and long runs. Arvin and Barillas (2002) study of some countries in Asia, Latin America, Caribbean, and Africa, found that aid had no impact on poverty reduction in the Africa sub-samples of North Africa and SSA for the period 1975 to 1998 studied.…”
Section: Foreign Aidmentioning
confidence: 95%
“…Evidence on the growth effects of international trade from extant studies has been more positive than that of FDI and foreign aid. International trade promotes domestic employment, enhances the transfer of technology between countries, and can help domestic firms to gain competitive advantage (Evans & Kelikume, 2018). However, similar to the effects of FDI and aid, results of empirical studies of the effects of trade on growth presents mixed evidence.…”
Section: Foreign Tradementioning
confidence: 99%
“…In line with Khadaroo and Seetanah (2007), Evans and Kelikume (2018), and Adeola et al (2018), the proxy for tourism demand is the total number of tourist arrivals. The lagged value of tourist arrivals serves as a proxy for taste formation as consumption of tourism depends on previous levels.…”
Section: Methodsmentioning
confidence: 99%
“…A review of literature points not only to the fact that there is a trend towards de-globalisation but also that countries most dependent on the global economy in terms of trade, tourism and remittances will be adversely affected. Evans and Kelikume (2018) discuss the positive impacts of trade, remittances and tourism on welfare with some other variables. Furthermore, Ghali (1976) writes about the positive impact of tourism on growth.…”
Section: Review Of Literaturementioning
confidence: 99%